PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS PASIEN DI RUMAH SAKIT AWAL BROS PEKANBARU - Citra Cahaya Sari; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In this research Issue is the decline in the number of outpatients in the last 3 years, especially for the old outpatients. This indicates patient loyalty to decline medical treatment to hospitals Early Bros Pekanbaru. As for the purpose of this research is to know the implementation of the marketing mix and knowing the loyalty of outpatients at the hospital Beginning Bros Pekanbaru. In addition to knowing the influence of marketing mix to the loyalty of patients in hospitals Early Bros Pekanbaru. Data collection through the kusioner of 100 outpatients. Results of research on the marketing mix implemented Early Bros Hospital Soweto rated it good. So too with the loyalty of outpatients at the hospital Beginning Bros Pekanbaru. votes have been good. However there are still shortcomings in the process and the price problem including outpatient medical treatment procedures. Results of calculation with the SPSS program, obtained as a result of that marketing mix (X) have a very strong relationship to patient loyalty (Y). Outpatient in the hospital Beginning Bros PekanbaruKeywords: marketing mix, patient loyalty, hospitals early bros pekanbaru